Diskriminasi dan Kekerasan terhadap Perempuan dalam Bidara Biduri karya Gde Artawan: Kajian Feminisme Sastra - Wisiani, Ni Luh Putu; Yasa, I Nyoman; Dewantara, I Putu Mas (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This research examines discrimination and violence against female characters in Gde Artawan's novel 'Bidara Biduri', focusing on how these issues are portrayed and experienced by the characters. The study aims to analyze and critically evaluate the representation of discrimination and violence against female characters in the novel. Employing Simon de Beauvoir's feminist theory within a descriptive qualitative framework, the research utilizes literary analysis methods for data collection. Findings are organized and analyzed through identification, description, explanation, and classification to address the research questions. The analysis reveals multiple forms of discrimination and violence against female characters, including stereotyping, subordination, neglect, and various types of abuse (psychological, physical, verbal, and domestic). Key examples include Westri, who faces stereotyping and verbal abuse due to her profession as a dancer; Leny, who experiences neglect and verbal/psychological violence related to infertility; and Luh Can/Luh Sandat, who suffers domestic violence encompassing psychological, verbal, and physical abuse. This research contributes to the understanding of gender-based discrimination and violence in Indonesian literature, highlighting the need for further exploration of these themes in contemporary works.